CODE SWITCHING AND CODE MIXING USED BY INDONESIAN ENGLISH TEACHER - rizka aziza puteri (Language-Edu, 2020)
This research is attentive to the sorts of CS and CM, the frequency, and the reasons used to code switch and code mix in the class used by the teacher of SMAN 7 Banjarmasin. The design is used in qualitative and quantitative research. The form of percentages using a quantitative approach then discussed, analyzed, and explained using a qualitative approach. The sources of the data are the teacher utterances that contain CS and CM. In results, there are three types of CS and CM that are used by the teacher. The types of CS are intra-sentential, inter-sentential, and tag switching. The types of CM are intra-lexica, intra-sentential, and involving a change of pronunciation. The teacher always uses CS more than CM. The teacher often to use CS inter-sentential. Then, the teacher often uses CM intra-sentential. The research shows there are six reasons to use CS and CM in a classroom. They are the rhetoric reason, the topic of conversation, being emphatic, interjection, repetition used for clarification, and softening and strengthening request or command. Then, there are three reasons to use CS and CM in the classroom. They are the rhetoric reason, repetition used for clarification, and softening and strengthening request or command.